Chemosis as an Initial Presentation of Systemic Lupus Erythematosus - Carvy Floyd Luceno; Minho Yu; Daniel I. Kim; Vaneet K Sandhu (Case Reports in Rheumatology)
Systemic lupus erythematosus (SLE) can present in a multitude of ways, which can be confounding and misleading for a clinician. Chemosis as an initial presentation is rare and has only been documented on a few case reports. However, when present, simultaneous involvement of other organs is likely. We present a previously healthy 29-year-old male who presented with severe bilateral chemosis and was subsequently diagnosed with SLE and antiphospholipid syndrome. Complications included multiple acute cerebral infarcts, lupus psychosis, lupus pleuritis, and lupus nephritis. The patient recovered well with appropriate treatment and chemosis ultimately resolved. Recognizing chemosis as an initial presentation of SLE is vital for appropriate evaluation and timely treatment to prevent disease progression.